Independent origin of sex chromosomes in two species of the genus Silene - Mrackova, Martina; Nicolas, Michael; Hobza, Roman; Negrutiu, Ioan; Monéger, Françoise; Widmer, Alexander; Vyskot, Boris; Janousek, Bohuslav (Genetics, 2008)
Here we introduce a new model species, Silene colpophylla, that could facilitate research of sex chromosome evolution and sex-determining systems. This species is related to the well-established dioecious plant model Silene latifolia. Our results show that S. colpophylla is, similarly to S. latifolia, a male heterogametic species, but its sex chromosomes have evolved from a different pair of autosomes than in S. latifolia. The results of our phylogenetic study and mapping of homologs of S. latifolia X-linked genes indicate that the sex determination system in S. colpophylla evolved independently from that in S. latifolia. We assert that this model species pair will make it possible to study two independent patterns of sex chromosome evolution in related species.
Keywords: modely genetické; Phylogeny; druhová specificita; Biological Evolution; Genes, Plant; Amplified Fragment Length Polymorphism Analysis; rostlinné geny; Species Specificity; biologická evoluce; Models, Genetic; Silene; analýza polymorfismu délky amplifikovaných restrikčních fragmentů; fylogeneze; chromozomy rostlin; Chromosomes, Plant